1996
DOI: 10.1523/jneurosci.16-02-00497.1996
|View full text |Cite
|
Sign up to set email alerts
|

Increased antioxidant enzyme activity in amyloid beta protein-resistant cells

Abstract: Clones of the rat pheochromocytoma cell line PC12 were selected for their resistance to amyloid beta protein (A beta). These A beta-resistant cells also survive higher concentrations of exogenously applied peroxides than the parent cells. A beta triggers intracellular H2O2 accumulation in the parent PC12 cells but not in the A beta-resistant cells. The absence of H2O2 accumulation in A beta-resistant cells is not attributable to differences in A beta binding to the cell surface. However, the mRNA and protein l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
123
0
4

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(138 citation statements)
references
References 0 publications
11
123
0
4
Order By: Relevance
“…Although difficult to study in patients, models of A␤ resistance have been generated in vitro following the continual exposure of cultured nerve cells to concentrations of A␤ that would otherwise be toxic and the eventual emergence of surviving clonal nerve cell populations. Analysis of these A␤-resistant nerve cells revealed up-regulation of anti-oxidant enzymes compared with the sensitive parental cells (12,13). Additionally these cells displayed an increased resistance to a wide array of neurotoxins, suggesting that acquisition of A␤ resistance also confers resistance to a variety of environmental stresses (14).…”
Section: Alzheimer Disease (Ad)mentioning
confidence: 97%
“…Although difficult to study in patients, models of A␤ resistance have been generated in vitro following the continual exposure of cultured nerve cells to concentrations of A␤ that would otherwise be toxic and the eventual emergence of surviving clonal nerve cell populations. Analysis of these A␤-resistant nerve cells revealed up-regulation of anti-oxidant enzymes compared with the sensitive parental cells (12,13). Additionally these cells displayed an increased resistance to a wide array of neurotoxins, suggesting that acquisition of A␤ resistance also confers resistance to a variety of environmental stresses (14).…”
Section: Alzheimer Disease (Ad)mentioning
confidence: 97%
“…Sagara et al (40) found that cells resistant to 〈␤ toxicity had elevated levels of catalase and GPx. The activity of both enzymes was reduced in rat brains exposed to 〈␤.…”
mentioning
confidence: 99%
“…In particular, Pappolla et al and Lovell et al found that catalase was associated with senile plaques in human brain sections from patients with AD (6,41). Several groups have shown that transfection of cells with catalase (40) or addition of catalase to the extracellular environment of cultured cells protected cells from 〈␤ toxicity (11,38). This cytoprotective effect was attributed to a catalase-induced reduction of the H 2 O 2 concentration outside and inside the cells, because H 2 O 2 readily diffuses across cell membranes (25,43).…”
mentioning
confidence: 99%
“…31 Interestingly, these A␤-resistant clones are also resistant to other oxidative into a foe and vice versa. stressors such as peroxides and the neuroleptic drug haloperidol, 71,72 which can induce oxidative memAcknowledgements brane damage in high concentrations. 73 The A␤-resistant cells have increased levels and activities of the We thank Patrick Baeuerle for the NF-B reporter plasantioxidant enzymes catalase and glutathione peroximid and we are grateful to Florian Holsboer for ongodase.…”
mentioning
confidence: 99%
“…73 The A␤-resistant cells have increased levels and activities of the We thank Patrick Baeuerle for the NF-B reporter plasantioxidant enzymes catalase and glutathione peroximid and we are grateful to Florian Holsboer for ongodase. 71 …”
mentioning
confidence: 99%